Hubungan antara kemampuan berpikir kritis dengan kemampuan komunikasi matematis siswa SMP pada pembelajaran matematika - Fahriza Noor; Mayang Gadih Ranti (STKIP PGRI Banjarmasin, 2019)
This research aims to identify the correlationof Critical Thinking and Mathematical Communication Ability.Critical thinking is an ability to clarify and improve understanding which aids in drawing appropriate conclusions and making the best decisions. Mathematical Communication is an ability to express mathematical idea written or orally. The research method is descriptive method. The Populations of research were all students of SMPN 1 Banjarbaru year VII. The sample of Population were 56 students of class VII A and VII B. The Data was collected by a test. The data was analyzed use Spearman Correlation Test. Spearman Correlation Test results shows that significance was 0,00 < 0,01, then Ho was rejected and the conclusion was there is a correlation of crtical thinking ability and mathematical communaction ability.